Is Surgical Treatment an Option for Locally Advanced Cervical Cancer in the Presence of Central Residual Tumor after Chemoradiotherapy? - Topuz, Samet; Kaban, Alpaslan; Küçücük, Seden; Salihoglu, Yavuz (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To evaluate the outcomes of surgical treatment in patients with chemoradiotherapy (CRT)-resistant and locally advanced cervical cancer (LACC).Methods Patients with LACC who underwent surgery due to resistance to CRT between 2005 and 2015 were reviewed retrospectively. Disease-free survival (DFS) and overall survival (OS) related factors were analyzed.Results A total of 23 patients were included in the study and the median age was 51 years old. A total of 14 patients (60.8%) experienced recurrence; among these recurrences, 8 of them were local, 5 were distant, 1 was both distant and local. A total of 9 patients (39%) died. The Median DFS and OS durations were 15 and 32 months, respectively. A total of 17 patients (74%) had undergone simple hysterectomy, 4 (17%) radical hysterectomy, and 2 (9%) total pelvic exenteration. Postoperative grade 3 and 4 complications were seen in 12 patients (52%). Macroscopic tumor presence in the pathology specimen was associated with distant recurrence and positive surgical margins with local recurrence (Log-Rank test p = 0.029 and p = 0.048, respectively). The only factor associated with OS was surgical margin positivity (Log-Rank test p = 0.008). The type of surgery, grades 3 and 4 postoperative complications, brachytherapy, and tumor histology were not associated with recurrence.Conclusion In patients with LACC, hysterectomy is an option in the presence of a central residual tumor after CRT. However, the risk of grades 3 and 4 complications of performed surgery is high. The presence of macroscopic tumor in the pathology specimen and positive surgical margins are poor prognostic factors. The goal of the surgeon should be to achieve a negative surgical margin. It does not seem important if the surgery is simple or radical.
Keywords: cervical cancer; brachytherapy; chemoradiotherapy; recurrence; resistant tumor